Development Of Comic Media For Arts And Culture Based On Local Wisdom - A. Nasywa Fairuz Zahirah; Khaerun Nisa'a Tayibu; Firdha Razak (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2026)
The limited introduction of local culture, especially the culture of Pangkep Regency to elementary school students, which is in line with the impact of the development of the era and technology, should encourage teachers to develop media that can help students recognize their area. The purpose of this study was to determine the characteristics of the Misteri Peti Warisan Bugis comic media and to describe the process of developing the Misteri Peti Warisan Bugis comic for students based on the stages of the ADDIE development model. The type of research is Research and Development (R&D) with a descriptive-quantitative approach. Data were obtained through observation sheets, questionnaires, and learning outcome tests, then analyzed with validity and reliability tests. The results showed that the Misteri Peti Warisan Bugis comic media has characteristics that attract the attention of teachers and students, help in learning, include local wisdom of Pangkep Regency, and produce new understanding in students, in addition, the procedure for developing the Misteri Peti Warisan Bugis comic media with the ADDIE model through the stages of analysis, design, development, implementation, and evaluation obtained a category that is feasible or valid, reliable, practical and effective.